Repression and Resistance: A Foucauldian Discourse Analysis of Power Structures in the Novel A God in Every Stone by Kamila Shamsie. - Ain Liaqat, Qurat Ul; Akhtar, Rizwan (Journal of Research in Humanities, 2019)
Human literary history is replete with both fiction and non-fiction narratives that chronicle intricate patterns of 'power' and its multiple manifestations. There are numerous modes through which power permeates societies and colonization is one of these many forms that have always been prevalent in all epochs and centuries. Literary texts, written by previously colonized nations, usually highlight the major characteristics of this recurrent historical phenomenon. A God in Every Stone (2014) by Kamila Shamsie is one of those novels that does not only illustrate the dynamics of colonization in the subcontinent but also pulls strands from historical eras to illustrate various manifestations of dominations. Michel Foucault's insights into the dynamics of power and resistance provide a suitable framework to evaluate the power patterns embedded in the structure of this novel. Therefore, this paper is a Foucauldian discourse analysis of hegemonic spatial structures, manufacturing of the colonized subjects, and historical strands of discursive practices of oppression that reinforce the multiple forms and levels of power in this narrative. The study argues that macro and micro forms of subjugations are imbued on numerous levels in this text. The narrative also highlights multiple forms of counteractive resistant forces which emanate as a reaction against colonization. Thus, this paper contends that Shamsie's novel contains a universal message of hope as it implies that although there are worldly gods in every stone of human history, however, resistance to those gods is imminent and endemic.